A Study on Stock Market Awareness among College and University Students in Ballari (International Journal of Food and Nutritional Sciences, 2022)
The stock market is a vital component of any modern economy, serving as a platform for businesses to raise capital and for investors to earn returns on their investments. Despite its importance, however, many young people, particularly undergraduate students, lack a basic understanding of how the stock market works and the potential benefits of investing in it.This research paper aims to explore the level of awareness and understanding of the stock market among undergraduate students. The study will assess the students' familiarity with key concepts and terminology related to the stock market, as well as their attitudes and perceptions towards investing in the stock market. Additionally, the research will examine the factors that influence these students' decisions to invest or not to invest in the stock market.This study focuses on student stock market awareness. The purpose of this study is to analyse students' degree of knowledge about the stock market and to investigate the elements that influence their interest and awareness in this sector. A survey questionnaire is used in the study to obtain data from a sample of students from various academic areas. According to the findings, students' awareness of the stock market is moderate, with many students having inadequate knowledge of the issue. Gender, age, academic discipline, and parental wealth were revealed to be important influences on students' stock market interest and awareness.